2011
DOI: 10.1186/1478-811x-9-15
|View full text |Cite
|
Sign up to set email alerts
|

LiCl induces TNF-α and FasL production, thereby stimulating apoptosis in cancer cells

Abstract: BackgroundThe incidence of cancer in patients with neurological diseases, who have been treated with LiCl, is below average. LiCl is a well-established inhibitor of Glycogen synthase kinase-3, a kinase that controls several cellular processes, among which is the degradation of the tumour suppressor protein p53. We therefore wondered whether LiCl induces p53-dependent cell death in cancer cell lines and experimental tumours.ResultsHere we show that LiCl induces apoptosis of tumour cells both in vitro and in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 46 publications
(53 reference statements)
0
21
0
1
Order By: Relevance
“…Inhibition of Hh and GSK-3 pathways reduces proliferation and induces apoptotic cell death of tumor cells in vitro and in vivo [9, 10, 23, 24]. …”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of Hh and GSK-3 pathways reduces proliferation and induces apoptotic cell death of tumor cells in vitro and in vivo [9, 10, 23, 24]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, lithium has been shown to inhibit cellular proliferation in combination with the regulation of the expression of genes involved not only with the apoptosis signaling pathway [Zhang et al, ] but also with the production of inflammatory cytokines [Matsebatlela et al, ] . In CRC, lithium induced apoptosis through a mechanism that is independent of p53 activity with increased production of TNF‐α and FasL, two death‐receptor ligands that activate the extrinsic apoptosis pathway [Kaufmann et al, ]. Whether this mechanism occurs in our models remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that inhibition of GSK3β promotes apoptosis in glioma cells and PDA cells [49], [50], and sensitizes PANC-1 cells to gemcitabine [51]. In addition, lithium induces apoptosis of a variety of cancer cells [36], [52]. At present, the mechanism of lithium-mediated anti-cancer activity is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been suggested that lower cancer prevalence observed in mental patients is likely due to benefit from protection of lithium treatment [34]. At the molecular level, lithium has been shown to inhibit the growth and/or tumorigenicity of cancer cells by modulating the biologic activities of many cancer related genes, for example, STAT3 [35], β-catenin/WNT [30], [31], TNF [33] and FASL [36], and P53 [37].…”
Section: Introductionmentioning
confidence: 99%